RUTTING ON THE SURFACES OF NON-RIGID ROAD PAVEMENTS: ANALYSIS OF THE CAUSES AND RECOMMENDATIONS FOR REDUCING - A. S. Aleksandrov; T. V. Semenova; A. L. Kalinin (Вестник СибАДИ)
Introduction. The works of reducing the intensity of rutting on the roads are relevant nowadays. Activities of improving the stability of road pavements include solving material problems, improving methods of calculation of structures and the development of new technologies to ensure high quality construction.Materials and methods. The analysis of data of natural and laboratory experimental researches established the reasons of formation of the rut on coverings of non-rigid road pavements. The authors presented the technique of experimental research of the tires passes’ distribution of vehicles on width of the traffic way and traffic lane. Moreover, the authors gave the coefficients for calculating the number of loads in the central and marginal parts of the coasting strips as well as in the inter-track space.Results. As a result, the authors suggested designs of road pavements with hidden rut elements, which placed on a surface of a highway subgrade on the basis of road pavement.Discussion and conclusions. As a result of the close proximity of the hidden track elements from each other, the soil of the subgrade between them experiences compression, in which the stress deviator is of the least importance compared to other stresses of the subgrade due to triaxial compression arising from both the moving load and its own weight pavement. The suggested variant helps to reduce significantly the deformation. For the successful implementation of hidden rut pavement, it is necessary to develop a new or reasonably choose a well-known method of calculating the depth of the rut, which is necessary to verify the criterion of gauge formation in the calculation of the thickness of hidden rut elements and the thickness of the pavement.The authors have read and approved the final manuscript. Financial transparency: the authors have no financial interest in the presented materials or methods. There is no conflict of interest.